Peran Aplikasi Bibit dalam Meningkatkan Literasi Investasi Syariah pada Gen Z - Dini Selasi; Muhammad Ahfas; Nunung Sinta Nuriyah (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
This study uses a Qualitative approach by comparing it with a descriptive method through secondary analysis by reviewing various literatures that are in accordance with the topic of discussion taken. This journal article was created with the aim of providing a deeper understanding of Generation Z's investment interests by explaining and presenting them comprehensively.This study reveals that Bibit has succeeded in capturing Generation Z's interest in investing in a simple way and in line with sharia values, without requiring large capital or in-depth financial knowledge. However, this study also highlights limitations, especially regarding the diversity of sharia products and the need for more in-depth training for beginners. The findings show that although Bibit plays an important role as a relevant sharia education and investment platform for Generation Z, there is still room for further development.